2007
DOI: 10.2169/internalmedicine.46.0237
|View full text |Cite
|
Sign up to set email alerts
|

Activations of Coagulation and Fibrinolysis Secondary to Bowel Inflammation in Patients with Ulcerative Colitis

Abstract: Background Recent investigations suggest that activation of coagulation and fibrinolysis occurs in patients with ulcerative colitis (UC). activated partial thromboplastin time (APTT), thrombin time (TT), prothrombin time (PT), serum concentrations of von Willebrand factor (vWF), activated factors XII, XI, X, IX, VIII, VII, V, II, fibrinogen, prothrombin fragments 1+2 (F1+2), thrombin-antithrombin complexes (TAT), protein S, protein C, plasminogen, α-2 plasminogen inhibitor (α-2PI) and D-dimer (D-D). Results Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 49 publications
1
68
0
1
Order By: Relevance
“…The activation of coagulation has been described also in other diseases characterized by inflammation, including other cutaneous disorders, such as bullous pemphigoid and angioedema due to C1 inhibitor deficiency [5][6][7][8], and a wide spectrum of systemic inflammatory diseases, such as rheumatoid arthritis [9] inflammatory bowel diseases [10] and sepsis [11]. This should not necessarily lead to consider activation of the coagulation as a nonspecific phenomenon, but rather to think that different diseases share, at different sites, a common intermediate step in their pathophysiology.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The activation of coagulation has been described also in other diseases characterized by inflammation, including other cutaneous disorders, such as bullous pemphigoid and angioedema due to C1 inhibitor deficiency [5][6][7][8], and a wide spectrum of systemic inflammatory diseases, such as rheumatoid arthritis [9] inflammatory bowel diseases [10] and sepsis [11]. This should not necessarily lead to consider activation of the coagulation as a nonspecific phenomenon, but rather to think that different diseases share, at different sites, a common intermediate step in their pathophysiology.…”
mentioning
confidence: 97%
“…Thus, in the skin microenvironment of CU and bullous pemphigoid, eosinophils express TF which activate coagulation and generate vascular permeability mediators. In angioedema due to C1-inhibitor deficiency, another skin disease characterized by increase in vascular permeability, there is an activation of blood coagulation [7,8], but edema is mediated by bradykinin generated upon activation of the contact system. An obvious concern with these views comes from the observation that markers of thrombin generation like F1 ?…”
mentioning
confidence: 99%
“…Third, the specificity and sensitivity of the two tests were different. Some studies 22,23) have reported that fibrinolysis may be associated with inflammation. However, in accordance with the previous study by Girona,7) our study showed no correlations between FDP, EPL, LY30, CL30, and ESR, which indicated inflammation may not play a role in fibrinolysis in patients with TA.…”
Section: Discussionmentioning
confidence: 99%
“…TAT complex concentrations were also assayed in order to determine whether possible haemostatic alterations resulting from babesiosis were associated with thrombin formation, since the identification of TAT complexes is often used in humans as an indicator of thrombin generation in different pathophysiological states such as arterial hypertension (Matyszko and Tymcio, 2008), ulcerative colitis (Kume et al, 2007) and diabetes mellitus (Gentile et al, 2007). TAT complexes were also elevated in dogs with chronic congestive heart failure and lower AT III activity compared to control groups (Tarnow et al, 2007).…”
Section: Discussionmentioning
confidence: 99%